Thermal Properties and Kinetics of Al/α-MnO2 Nanostructure Thermite - Song,Jia-Xing (2018)
In this work, thermal properties and kinetics of Al-nanoparticles/α-MnO2 nanorods thermite were reported. The α-MnO2 nanorods were synthesized using a hydrothermal method and were characterized by X-ray powder diffraction (XRD) and X-ray photoelectron spectra (XPS), then combined with Al nanoparticles based on the ultrasonic mixing method to prepare the nanostructure thermite. Besides, both pure components and mixture were characterized by field emission scanning electron microscopy (FE-SEM) to observe their morphologies and structures. Subsequently, the thermal properties of Al/α-MnO2 nanostructure thermite were studied on the basis of thermogravimetric-differential scanning calorimetry (TG-DSC). According to the TG-DSC tests, the calculation results of activation energy for kinetics of Al/α-MnO2 thermite were obtained using different isoconversional methods. It was found that Al/α-MnO2 nanostructure thermite has high heat release and low onset temperature, and the heat release of the nanostructure thermite was approximately 1146.6 J g -1.